Centhaquine Restores Renal Blood Flow and Protects Tissue Damage After Hemorrhagic Shock and Renal Ischemia - Ranjan, Amaresh K.; Zhang, Zhong; Briyal, Seema; Gulati, Anil (Frontiers in Pharmacology, 2021)
Background- Centhaquine (CQ) (Lyfaquin®) is in late stage clinical development as a safe and effective first-in-class resuscitative agent for hemorrhagic shock patients (NCT02408731, NCT04056065 and NCT04045327). Acute kidney injury (AKI) is known to be associated with hemorrhagic shock. Hence, effect of CQ on protection of kidneys from damage due to hemorrhagic shock was investigated. Methods- To assess effect of CQ on AKI in shock, we created a rat model with hemorrhagic shock and AKI. Renal arteries were clamped and de-clamped to induce AKI like ischemia/reperfusion model and hemorrhage was carried out by withdrawing blood for 30 min. Rats were resuscitated with CQ (0.02 mg/kg) for 10 min. MAP, heart rate (HR), and renal blood flow (RBF) were monitored for 120 min. Results- CQ produced a significant improvement in RBF compared to vehicle (p<0.003) even though MAP and HR was similar in CQ and vehicle groups. Blood lactate level was lower (p=0.0064) in CQ than vehicle at 120 min post-resuscitation. Histopathological analysis of tissues indicated greater renal damage in vehicle than CQ. Western blots showed higher HIF1-A (p=0.0152) and lower NGAL (p=0.01626) levels in CQ vs vehicle. Immunofluorescence in the kidney cortex and medulla showed significantly higher (p<0.045) expression of HIF1-A and lower expression of Bax (p<0.044) in CQ. Expression of PHD 3 (p<0.0001) was higher, while the expression of Cytochrome C (p=0.01429) was lower in the cortex of CQ than vehicle. Conclusions- Results show CQ (Lyfaquin®) increased renal blood flow, augmented hypoxia response, decreased tissue damage and apoptosis following hemorrhagic shock induced AKI, and may be explored to prevent/treat AKI. Translational Statement- Centhaquine (CQ) is safe for human use and currently in late stage clinical development as a first-in-class resuscitative agent to treat hemorrhagic shock. In the current study, we have explored a novel role of CQ in protection from hemorrhagic shock induced AKI, indicating its potential to treat/prevent AKI.